2012
DOI: 10.1016/j.yqres.2012.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Assessing lithologic discontinuities and parent material uniformity within the Texas sandy mantle and implications for archaeological burial and preservation potential in upland settings

Abstract: Alfisols within the Texas Gulf Coast Plain commonly exhibit textural contrasts between sandy, artifact-bearing A–E horizons (i.e., sandy mantle), and artifact-sterile clay-rich Bt (argillic) horizons. This has invoked debate about parent material uniformity and pedogenic versus geomorphic sandy mantle origins, which has implications for the scientific value of buried archaeological sites. To improve our understanding of archaeological burial in upland settings, we evaluated parent material uniformity within fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…Results of the Ward clustering confirmed that the profile differences in particle size distribution in Retisols is mainly a result of translocation of the finest particles from the eluvial horizons to illuvial ones (Marcinek and Wioelañska 1984, Komisarek 2000, Komisarek and Sza³ata 2008, although in the pedons studied an abrupt change in particle size distribution is found. This interpretation is in agreement with the results reported by Ahr et al (2012Ahr et al ( , 2013 for sandy mantle Alfisols of the Texas Gulf Coastal Plain. CONCLUSIONS 1.…”
Section: Resultssupporting
confidence: 93%
“…Results of the Ward clustering confirmed that the profile differences in particle size distribution in Retisols is mainly a result of translocation of the finest particles from the eluvial horizons to illuvial ones (Marcinek and Wioelañska 1984, Komisarek 2000, Komisarek and Sza³ata 2008, although in the pedons studied an abrupt change in particle size distribution is found. This interpretation is in agreement with the results reported by Ahr et al (2012Ahr et al ( , 2013 for sandy mantle Alfisols of the Texas Gulf Coastal Plain. CONCLUSIONS 1.…”
Section: Resultssupporting
confidence: 93%
“…A critical component of pedogenic research is the assessment of potential parent material nonuniformity (i.e., the presence of lithologic discontinuities [LDs]; Ahr et al., 2012; Schaetzl, 1998; Schaetzl, Kasmerchak, et al., 2020). Assessment of parent material uniformity is usually done by examining the vertical distribution of immobile particle size separates, particularly sands, and/or slowly weatherable index elements (e.g., Zr and Ti).…”
Section: Methodsmentioning
confidence: 99%
“…Because LDs often form as a result of changes in depositional environments, abrupt dissimilarities in the concentration of these components with depth are considered an indicator of parent material nonuniformity (Soil Survey Staff, 2014b). We conducted our evaluation on a pedogenic (mobile) constituent‐free basis, so as to not mathematically bias data on the immobile skeletal fraction (Ahr et al., 2012; Soil Survey Staff, 2014b), by focusing on data from the medium and fine sand subfractions, because of their greater abundance. Additionally, we used Zr and Ti data derived from the pXRF to evaluate index element distribution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation